Automatic Transfer Switch System Design on Solar Cell – Grid Hybrid Based on Android Application - Mairizwan Mairizwan; Washilla Audia; Yulkifli Yulkifli; Aditya Rinaldi (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2022)
The main source of electricity supply, namely PLN, greatly affects the supply of electricity and is not always continuous in its distribution. PLN power outages cause the distribution of human activities and productivity. The solution is to create a hybrid automatic transfer switch (ATS) system. The system works automatically as a hybrid power plant using a solar cell and PLN using ATS and remote monitoring using android. This type of research is classified as laboratory experimental engineering research. This study aims to determine the power savings of PLN that flows to the load after using the ATS system, work specifications, and system design specifications. In this study, a solar cell with a maximum capacity of 20 watts was used. The results of power savings after using the ATS system in sunny weather conditions for 10 hours of irradiation with an average solar intensity of 318,551 lux is 16,84%. The system performance specifications are small, portable, and easy to operate. The values of accuracy and precision in power saving are 96,13% and 95%.